Principles of electrical grid configuration management and tasks of their implementation - A. V. Vinogradov; A. V. Vinogradova; A. Yu. Seyfullin; A. V. Bukreev; V. E. Bolshev (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. To consider and analyze the definitions of the concepts "configuration of the electrical grid", "control of the configuration of the electrical grid ", "parameters of the configuration of the electrical grid ". To justify the need to manage the configuration of electrical grid, describe the principles and methods of managing the configuration of the electrical grid. To demonstrate the implementation of the principles of managing the configuration of the electrical grid on the example of an electrical grid with a nominal voltage of 0.4 kV with the use of proprietary technical configuration management tools. METHODS. Based on the literature review, the study identified the wording of key concepts, such as" configuration of the electrical grid"," management of the electrical grid configuration", "parameters of the electrical grid configuration". Methods of managing the configuration of the electrical grid are shown. The principles of electrical grid configuration management proposed by the authors are considered, which include observability, manageability, segmentability, flexibility of the electrical grid configuration, equipment intellectualization, and integration into the economy. The essence of each of the management principles is revealed and the effects of their implementation are shown. The effects of implementing the configuration management principles are to reduce the number of power supply interruptions and reduce the time of power supply interruptions to consumers, mismatch the quality parameters of the electricity supplied to them, as well as to increase the availability of electricity infrastructure. The rationale for the need to manage the configuration of electrical grid is given. Within the framework of the conducted research, the method of system analysis, methods of comparisons and analogies, and expert assessments were used. RESULTS. On the example of the scheme of power supply to consumers at a voltage of 0.4 kV, the implementation of the principles of control of the configuration of electrical grid with the use of proprietary technical means – multi-contact switching systems, input-accounting-distribution devices integrated into the monitoring systems of the parameters of the operating modes of electrical grid and other devices is illustrated. CONCLUSION. The implementation of the principles of configuration management of electrical grid allows to increase the efficiency of power supply systems for consumers and at the same time causes the need to develop new technical means of automation and monitoring of parameters of operating modes of electrical grids.